Relation subsidence and water level of peatland cultivated with oil palm in Riau, Indonesia. Issue 1 (May 2021) - Wasilul Lutfi, M; Baskoro, D P T; Anwar, S; Pulunggono, H B
Abstract: This study was aimed to determine the relation changes in the subsidence and the depth of water level of peatlands cultivated with oil palm. The research site is the oil palm plantations in Koto Village, Gasib District, Siak Regency, Riau, Sumatera. The observations were in 4 blocks, namely block L1 (shrubs), Block D1 (oil palm aged 15 years), D8 (oil palm aged 10 years), and D31 (oil palm aged 20 years). Research parameters include peat subsidence and groundwater level. The results showed that the value of peat subsidence was fluctuative. This fluctuation was due to the rise and fall of the groundwater level. The highest rate of decline is shown in block L1 with 0.75 cm y −1 with SD 1.03 and the groundwater level in D1 with 52 cm. The water level is influenced by the condition of the monthly rainfall. The correlation between land subsidence and peat water level shows a close and significant relationship (p <0.01, r = 0.871).